Validation of the Omron M3 Intellisense (HEM-7051-E) Upper Arm Blood Pressure Monitor, for Self-Measurement, According to the European Society of Hypertension International Protocol Revision 2010 in a Stage 3-5 Chronic Kidney Disease Population - Akpolat, Tekin; Erdem, Emre; Aydogdu, Turkan (Karger, 2012)
Background: Encouragement of home blood pressure (BP) monitoring has a great potential to improve hypertension control rates. The purpose of this study was to test validation of the Omron M3 Intellisense (HEM-7051-E) upper arm BP measuring monitor for self-measurement according to the European Society of Hypertension International Protocol revision 2010 (ESH-IP2) in stage 3-5 chronic kidney disease (CKD) patients. Methods: 66 patients having CKD stage 3-5 were included in the study. Nine consecutive measurements were made according to the ESH-IP2 protocol. Results: The Omron M3 Intellisense device fulfills the validation criteria of the ESH-1P2 for stage 3-5 CKD patients. Conclusion: Although arterial stiffness can affect accurate BP measurement, there are limited data regarding the use of automated oscillometric devices in CKD. To our knowledge, this is the first study investigating validation of an oscillometric device in stage 3-5 predialysis CKD patients. This study validates the Omron M3 Intellisense upper arm device for stage 3-5 CKD patients. New validation studies investigating other oscillometric sphygmomanometers for CKD patients and involvement of nephrologists in these studies have great potential to increase patient care in CKD. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Arterial Stiffness; Chronic Kidney Disease; Home Blood Pressure Monitoring; Hypertension; Oscillometric Sphygmomanometers; Validation Protocols